2005
DOI: 10.1016/j.clpt.2005.08.010
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study indicating that bradykinin B2 receptor antagonism attenuates protamine-related hypotension after cardiopulmonary bypass

Abstract: Increased bradykinin contributes to protamine-related hypotension through its B(2) receptor in ACE inhibitor-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Several studies had demonstrated that treatment with B1R or B2R antagonists ameliorated tissue damage in several pathologies [23][24][25][26]. B1R ability to be expressed exclusively in traumatized tissues indicates its close relationship with inflammatory responses.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies had demonstrated that treatment with B1R or B2R antagonists ameliorated tissue damage in several pathologies [23][24][25][26]. B1R ability to be expressed exclusively in traumatized tissues indicates its close relationship with inflammatory responses.…”
Section: Discussionmentioning
confidence: 98%
“…Although active thrombin seems to be the main source of t-PA release in in-vitro studies, [20] bradykinin appears to be the main stimulus for t-PA secretion during CPB. It has been shown that by blocking bradykinin receptors, [21] or by preventing the release of bradykinin by kallikrein inhibition, [22] t-PA release can be reduced. There seems to be a variability in the activation of the fibrinolytic system during CPB.…”
Section: Fibrinolysis and Surgerymentioning
confidence: 99%
“…It remains a standard of care in numerous cardiac surgical procedures, including aortic aneurysm repairs and bypass surgeries . Despite its widespread use, protamine sulfate suffers from a poor therapeutic index, increased incidences of hypersensitivity, and adverse outcomes such as vasoconstriction, arterial hypertension, hemorrhage, pulmonary edema, pulmonary hypertension, and bradychardia of the lungs by induction of classical complement activation, recruitment of inflammatory cells, and release of oxygen-free radicals. …”
Section: Polyanions That Inhibit Blood Coagulationmentioning
confidence: 99%